Additive Approximation Algorithms for Modularity Maximization - Kawase, Yasushi; Matsui, Tomomi; Miyauchi, Atsushi (arXiv.org, 2016)
The modularity is a quality function in community detection, which was introduced by Newman and Girvan (2004). Community detection in graphs is now often conducted through modularity maximization: given an undirected graph \(G=(V,E)\), we are asked to find a partition \(\mathcal{C}\) of \(V\) that maximizes the modularity. Although numerous algorithms have been developed to date, most of them have no theoretical approximation guarantee. Recently, to overcome this issue, the design of modularity maximization algorithms with provable approximation guarantees has attracted significant attention in the computer science community. In this study, we further investigate the approximability of modularity maximization. More specifically, we propose a polynomial-time \(\left(\cos\left(\frac{3-\sqrt{5}}{4}π\right) - \frac{1+\sqrt{5}}{8}\right)\)-additive approximation algorithm for the modularity maximization problem. Note here that \(\cos\left(\frac{3-\sqrt{5}}{4}π\right) - \frac{1+\sqrt{5}}{8} < 0.42084\) holds. This improves the current best additive approximation error of \(0.4672\), which was recently provided by Dinh, Li, and Thai (2015). Interestingly, our analysis also demonstrates that the proposed algorithm obtains a nearly-optimal solution for any instance with a very high modularity value. Moreover, we propose a polynomial-time \(0.16598\)-additive approximation algorithm for the maximum modularity cut problem. It should be noted that this is the first non-trivial approximability result for the problem. Finally, we demonstrate that our approximation algorithm can be extended to some related problems.